Aggregation pheromone 4, 8-dimethyldecanal and kairomone affect the orientation of Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae) adults. (December 2018) - Dissanayaka, D.M.S.K.; Sammani, A.M.P.; Wijayaratne, L.K.W.
Abstract: Tribolium castaneum, the red flour beetle, is a major pest of stored products throughout the world. The male T. castaneum adults biosynthesize and release the aggregation pheromone 4, 8-dimethyldecanal (4, 8 DMD), and the monitoring traps having the synthetic form of this pheromone and kairomone are commercially available. However, certain information available on the response of T. castaneum adults to the strength of pheromone and the nature of air flow is inadequate and thus limits the potential use of this compound. The objectives of this research were to determine if the orientation of adult beetles to the synthetic form of the pheromone 4, 8 DMD is affected by the distance from the pheromone, its concentration and air movement. Experimental design was completely randomized design with three replicates. The T. castaneum adults released at different distances from the pheromone placed at varying concentrations tested their orientation to the pheromone with the presence or absence of air flow. The control experiments were conducted without the pheromone. A separate experiment tested if exposure to 4, 8 DMD alters the direction of movement in T. castaneum adults. The maximum trap catch (24%) was obtained with 0.5 μL of 4, 8 DMD and when the beetles were released at distances up to 60 cm from the pheromone. The percentage of beetles trapped declined when the beetles were released 60–120 cm from the pheromone. The average angles on beetle turning during their orientation were significantly higher in the presence of pheromone than the respective controls. Air movement downstream of the pheromone trap increased the percentage beetles trapped compared to that in the absence of air flow. It is concluded that the orientation of T. castaneum adults is affected by the concentration of 4, 8 DMD, distance from the pheromone and the air movement. Highlights: The synthetic analogue of 4, 8-dimethyldecanal (4, 8 DMD) was used to determine the orientation of T. castaneum adults. Percentage beetles trapped was highest until 60 cm from the pheromone and decreased at longer distances. Of the concentrations tested, the adult beetles were trapped maximally at 0.5 μL of 4, 8 DMD. Air movement downstream of the pheromone increased the trap catch. Adult beetles altered the directions of movement when exposed to 4, 8 DMD.